A SAS macro to compute HUI summary and utility scores: An application to the Fit Blue study. Issue 1 (1st January 2019) - Kocak, Mehmet; Wang, Jiajing; Krukowski, Rebecca; Talcott, Wayne G.; Klesges, Robert C.
Abstract: The Health Utilities Index (HUI) questionnaire provides a mechanism to assess intervention effectiveness in multi-attribute health-related quality of life utilizing a set of health status classification systems. It is a comprehensive and valid questionnaire. The Dissemination of the Look AHEAD Weight Management Treatment in the Military (Fit Blue) study used the HUI system to assess the health status of its participants in US Military. HUI system assesses health status in 14 different domains (6 in HUI2 and 8 domains in HUI3) through a complicated utilization of a subset of 41 questions for each domain, and there is no readily available software that takes the raw data and computes the final scores of each domain as well as the corresponding multi-attribute utility function scores and single-attribute utility function scores to compare the health status of a given participant in a given health domain with healthy counterparts in the general population. In this study, we present a SAS ® Macro called %HUI that receives the raw HUI data and computes all domain scores as well as utility scores. We have tested the %HUI macro with the test data provided in the HUI manual and applied it to the HUI data from the Fit Blue study.